Morphological identification of fungi isolated from Garcinia mangostana plants - Cuervo-Parra , Jaime Alioscha; Romero-Cortes , Teresa; Román Aguilar , Raúl; Valle Hernández, Julio; Aparicio-Burgos, José E. (Revista Mexicana de Ciencias Agrícolas, 2024)
Mangosteen fruits possess several nutritional and nutraceutical properties important for human health, their cultivation is considered a production alternative for the tropical regions of Mexico. The objective of this research was to characterize morphologically pathogenic or antagonistic fungi isolated from plant tissues of mangosteen plants located in the municipality of Cacahoatán, Chiapas. In 2022, leaves and roots were collected from healthy plants, without characteristics of disease symptoms, fungi were isolated using the filter paper screening technique to obtain monosporic cultures, and morphological characterization was performed by scanning electron microscopy. Three fungal cultures were obtained, one from the rhizosphere Trichoderma asperellum and two in the leaves Rhizopus oryzae and Botrytis cinerea. A total of 25 measurements were taken to calculate the length and width of the following structures: sclerotia, columellae, conidia, conidiophores, phialides, and chlamydospores. The correct identification of the specific structures of the causative agents can help to propose strategies for disease control and prevention in mangosteen crops in the Soconusco region of the state of Chiapas, Mexico.
Keywords: Botrytis cinerea; Rhizopus oryzae; Trichoderma asperellum; mangosteen; rhizosphere